PREREQUISITES FOR THE INTRODUCTION OF THE COMMON TRANSIT PROCEDURE IN UKRAINE (INNOVATIVE ECONOMY, 2023)
Ruda T.V., Dziurhaliuk U.O. PREREQUISITES FOR THE INTRODUCTION OF THE COMMON TRANSIT PROCEDURE IN UKRAINEPurpose. The aim of the article is to study the prerequisites for the effective application of the common transit procedure in Ukraine.Methodology of research. The following research methods were used in order to achieve the defined goal of the study: induction and deduction, theoretical generalization, abstraction, dialectical cognition – when studying scientific sources and researching theoretical aspects of the implementation of the common transit procedure, determining the categorical apparatus of the selected issue; abstract and logical – for summarizing theoretical propositions, forming conclusions and proposals on the topic of research.Findings. The advantages and peculiarities of the implementation of the common transit procedure in Ukraine have been determined. The need to create appropriate conditions for the full implementation of this mechanism has been updated. First of all, this concerns the establishment of active work with business in order to maximize interest in the application of this customs procedure. It is noted that in order to attract participants of foreign economic activity to the application of the new program, a comprehensive approach should be used, following several directions at once, among which the integration of the domestic and European legal framework on the implementation of the common transit procedure, which is the basis for the successful implementation of the new direction, requires special attention.The need to prepare methodological recommendations, explanations, informational materials, presentations, etc., is outlined, which will make it possible to emphasize certain elements, advantages, and opportunities of the new system for participants in foreign economic activity. In addition, the expediency of ensuring close communication with business entities has been determined, through holding seminars, round tables, meetings, consultations and posting relevant information in the form of infographics and materials on the official website of the State Customs Service.Originality. Research into the theoretical aspects of providing prerequisites for the practical implementation of the common transit procedure and the use of the electronic transit system (NCTS) into the activities of domestic customs and subjects of foreign economic activity has gained further development.Practical value. The results obtained in the course of this study can be fully used in the process of developing scientifically based proposals regarding the conceptual directions of reforming customs procedures in Ukraine.Key words: transit, common transit, implementation of the customs procedure of common transit, electronic transit system (NCTS).
Keywords: transit; common transit; implementation of the customs procedure of common transit; electronic transit system (NCTS).